The canary in the coal mine: Tony Harrison and the poetics of coal, climate, and capital. Issue 5 (28th July 2016) - Thomas, David
ABSTRACT: This paper argues that Tony Harrison's poetic studies of deindustrialised Yorkshire anticipate Jason Moore's eco-Marxist critique of the neoliberal energy economy. Critical discussion of Tony Harrison's poetry has focused on the characteristic stances and techniques by which the poet first established his canonical standing, essaying his uneasy class consciousness and explosive use of regional dialect. Precious little attention has been paid to the ecological concerns that have become an increasingly integral element of Harrison's work. In the long narrative poem v . (1984) Harrison responded to the hard-fought Miners' Strike (1984–5), protesting the disenfranchisement of the British industrial working class. In some of v. 's more speculative lines, he countenanced the possibility of coal's eventual 'exhaustion'. In the film poem Prometheus (1998), he appraised the Miners' Strike from the distance of a decade, anchoring the poem in the perspective of a cancer-ridden coal miner. In the image of a dying, chain-smoking, Prometheus, Harrison cast the peculiar ironies of Britain's ongoing coal dependency in particularly profound relief. This paper finds that the evolution of Harrison's lyric voice captures much of the underlying music of British society, as it confronts the legacy of industrialisation, as history closes in, unremittingly, on capital's socioecological endgame.